Newcastle Disease Virus as Virotherapy Agent Targeting p53 in Rat Fibrosarcoma Models - I Putu Krisna Ardhia Pradnyandika; I Nyoman Mantik Astawa; Anak Agung Ayu Mirah Adi (Journal of Advanced Veterinary Research, 2023)
Repairing wild-type p53 or destroying of mutant p53 is one of the therapeutic targets in cancer. Newcastle disease virus (NDV) is a natural oncolytic virus that has potential as a virotherapy agent in cancer. This virus has been shown to induce cancer cell death. The aim of this study was to determine the expression of p53 in cytoplasm and nucleus of cancer cells and its correlation to the grade of cancer malignancy after NDV therapy in rat fibrosarcoma model. Rat fibrosarcoma model were divided into two groups, i.e., the control group (P0) and the treatment group (P1), each consist of 3 rats. The control group (P0) was injected with 0.5 mL phosphate buffered saline and treatment group (P1) was injected with 0.5 mL NDV Tabanan-1/ARP/2017 intratumorally once a day for four consecutive days. At the end of the study, 15 days post-treatment, all rats were euthanized and fibrosarcoma tissue was collected. Fibrosarcoma tissue was examined using immunohistochemistry to determine p53 expression and histopathological examination with hematoxylin-eosin staining to determine the grade of malignancy. The results of this study, the mutant p53 were more expressed in the control group (P0) than the treatment group (P1). It showed that NDV was significant (P<0.05) to the decrease of mutant p53 expression and positively correlated (P<0.05) to the cancer malignancy in rat fibrosarcoma model. In conclusion, NDV has potential as a virotherapy agent targeting mutant p53 in rat fibrosarcoma models.